The impact of service quality on customer satisfaction The case study of urban transport services in Mila city - agoun, charafe (Milev Journal of Research and Studies, 2016)
This study aims to determine the impact of the urban transport services quality through its dimensions: " service offering, ease of access, information, appointments (duration), customer care, welfare (comfort), security.", On customer satisfaction. The study found a significant impact of the urban transport services quality on customer satisfaction, and the presence of significant effect for only three dimensions: security, service offering, appointments (duration), on customer satisfaction